State, Religion, and Secularism: A Reinterpretation of Ali ‘Abd al-Raziq's Thought in the Context of Indonesian Democracy - Hidayatulloh, Taufik (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2025)
Abstract: Purpose- This study aims to reinterpret Ali ‘Abd al-Raziq’s thoughts on the separation of religion and politics within the framework of Indonesian democracy, offering fresh perspectives on the relationship between religion and the state in a pluralistic society. Design/methods/approach- The research adopts a library research method using a descriptive qualitative approach, analyzing primary texts by al-Raziq alongside relevant literature on Indonesian democratic principles and political theology. Findings- The study finds that al-Raziq’s arguments—particularly his rejection of the caliphate as a religious obligation and his emphasis on politics as a human construct—resonate with Indonesia’s foundational philosophy of Pancasila. His thought affirms the necessity of a state independent from religious authority while upholding the moral value of religion in social life. Research Implications- This reinterpretation highlights the continuing relevance of al-Raziq’s secular political theology in contemporary Muslim-majority democracies. It provides conceptual support for democratic systems that separate state governance from religious institutions while maintaining space for ethical-religious influence in public discourse.